1979
DOI: 10.1007/bf02307486
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of the bearing capacity of soil masses

Abstract: Calculation of the stress and strain of soil masses (foundations, dams, earth embankments, and slopes) to assure the maximum use of their bearing capacity should be done for any effects on them wlth consideration of the appearance and development of zones of limit stress in the soil. Such a Solution is realized in the mixed problem of the linear or nonlinear theory of elasticity and plasticity using a single model of elastoplastic soil at all loading stages [1]. The corresponding variants of its formulation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…An analysis of recent experimental and theoretical works [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] devoted to a study of the stability of sand bases under inclined static loads revealed substantial differences in a quantitative estimation of the bearing capacity of these bases. These estimates in various methods of calculation differed by a factor of 8-10, which forces one to doubt the reliability of their theoretical basis.…”
Section: Specifications)mentioning
confidence: 99%
“…An analysis of recent experimental and theoretical works [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] devoted to a study of the stability of sand bases under inclined static loads revealed substantial differences in a quantitative estimation of the bearing capacity of these bases. These estimates in various methods of calculation differed by a factor of 8-10, which forces one to doubt the reliability of their theoretical basis.…”
Section: Specifications)mentioning
confidence: 99%